Outcome of Two Ring Hybrid Ilizarov Fixator in the Management of Proximal Tibial Fractures in Adults. (Journal of Pakistan Orthopaedic Association, 2021)
Objective: To determine the functional and radiological outcome two ring hybrid Ilizarov fixator in the management of  proximal tibial fractures in adults.Methods: This descriptive study was conducted in department of Orthopaedic surgery Nishtar Medical University Multan from 5th May 2018 to 24th June 2020. All adults patients with  proximal tibial fractures meeting the inclusion criteria were treated with two ring hybrid Ilizarov fixator. Post operative functional outcome was assessed with knee range of motion and Rasmussen functional knee score and graded as excellent, good, fair and poor. Radiological outcome was assessed with fracture healing on radiographs. Comparative analysis of results were done after stratification of age, gender, type of fracture and time since fracture and P value calculated with Chi square test and student-t test. P value < 0.05 was considered significant.Results: The total number of patients in our study was 50.The mean age was 40.7 ± 10.16.Male patients were 45(90%) and female 5(10%). Shatzker type VI fractures were present in 30(60%) patients, Shatzker type V fractures in 11(22%), extra articular metaphyseal fractures in 5 (10%) and proximal one third shaft fractures in 4(8%) patients. All the fractures achieved union with mean union time 17.58±3.43 weeks. Functional outcome as per Rasmussen functional knee score was excellent outcome with more than 90° knee flexion in 32(64%) patients, good outcome and up to 90°flexion in 15(30%) and  fair outcome with 45°flexion at the knee in 3(6%) patients. Younger patients were able to tolerate early weight bearing than elderly (P=0.006) Patients with open fractures had lower Rasmussen score (P=0.043), decrease knee flexion (P=0.043), and increased pin tract infection (P=0.031).Conclusion: Proximal tibial fractures treated with two-ring hybrid Ilizarov fixator is an effective technique as excellent functional and radiological outcome was achieved in majority of our patients.